Introduction of Water Treatment in Slot‐Die Coated Organic Solar Cells to Improve Device Performance and Stability (Adv. Funct. Mater. 39/2022). (26th September 2022) - Han, Nara; Heo, Youn‐Jung; Lee, Minwoo; Moon, Yina; Yang, Dongseong; Kim, Yunseul; Kim, Dong‐Yu
Abstract : Organic Solar Cells In article number 2204871, Dong‐Yu Kim and co‐workers propose water treatment by inducing vortex agitation in the stirring process of the active solution for organic solar cells, which can yield good dispersion of donors and acceptors. The introduced water content for the water treatment is universally optimized in small (0.1 cm 2 ) and large (10 cm 2 ) organic solar cells with improved final device efficiency and stability.